Urological Carcinomas in Patients Presented with Gross Hematuria: Urological Carcinomas with Gross Hematuria - Asif, Muhammad; Chandio, Mumtaz Ali; Rehman, Obaid Ur; Safiullah, .; Akbar, Fazli; Mughal, R.A; Rafiullah, . (Pakistan Journal of Health Sciences, 2025)
Gross hematuria is a common urological symptom associated with both benign and malignant conditions. It is often a presenting feature of urological carcinomas, necessitating timely evaluation and diagnosis to improve outcomes. Objectives: To determine the prevalence of urological carcinomas and assess their association with demographic and clinical variables among patients presenting with gross hematuria. Methods: This descriptive cross-sectional study was conducted at the DHQ Teaching Hospital Mardan (KP) from July 2024 to January 2025. A total of 209 patients presenting with gross hematuria were included. Detailed demographic and clinical data, including age, gender, family history of cancer, anticoagulant use, urinary tract infections, history of stones, and prior urological surgeries, were recorded. All patients underwent urine cytology, ultrasound, X-ray KUB, computed tomography (CT) scan, and cystoscopy when required. Data analysis was performed using SPSS-25, and the Chi-square test was applied to determine associations. Results: Urological carcinoma was diagnosed in 41 (19.6%) patients. Higher prevalence was observed in older age groups (24.6% in 60–80 years) but showed no significant association with gender (p=0.333) or other clinical variables such as urinary tract infections (p=0.527) and anticoagulant use (p=0.997). Benign causes, including urinary tract infections (17.8%) and trauma, were common. Conclusions: It was concluded that urological carcinomas were prevalent in patients with gross hematuria, particularly in older age groups, highlighting the need for structured diagnostic evaluations. Early imaging, cytology, and cystoscopy are recommended to differentiate malignant from benign causes and improve outcomes.